2019
DOI: 10.1097/won.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalists' Needs Assessment and Perceived Barriers in Wound Care Management

Abstract: The purpose of this quality improvement (QI) project was to determine hospitalists' knowledge, practices, and perspectives related to management of pressure injuries (PIs) and neuropathic/ diabetic foot complications (having a foot ulcer or subsequent development of a foot infection because of a foot ulcer). We also sought to identify resources for and knowledge-based barriers to management of these wounds. This QI effort targeted an inter-disciplinary group of 55 hospitalists in internal medicine that consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
(18 reference statements)
2
16
0
Order By: Relevance
“…However, patient satisfaction is highly associated with having a language concordant provider. Furthermore, such association still remains regardless of the uency of the health care provider (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, patient satisfaction is highly associated with having a language concordant provider. Furthermore, such association still remains regardless of the uency of the health care provider (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies examining nurses' confidence in PI care similarly found that most nurses lack confidence. 27,28 Because the PI healing period takes between 9 and 21 weeks, 39 and patients stay in hospitals for an average of only 2 to 4 weeks in China, nurses do not gain self-efficacy from witnessing PIs heal. In addition, the same patient may receive PI care from many different nurses.…”
Section: Discussionmentioning
confidence: 99%
“…26 Nurses' reported self-efficacy in PI care varies, with ratings of confidence in providing PI care ranging from 12% to 90%. 27,28 Because self-efficacy is nurses' belief that the practice will produce the desired results, low self-confidence may lead them to practice less than what is recommended by the evidence-based practice guidelines. 29 It appears that many nurses provide skin care for patients with PI risk by relying primarily on their own knowledge and experience rather than regular use of assessment tools and practice guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly central keywords identified in this study were as follows: ‘wound’, ‘injury’, ‘dressing’, ‘breast’, ‘temperature’, ‘drainage’, ‘diabetes’, and ‘cleaning’. These keywords suggest that overall wound management, including dressing and drainage, is an important topic in the field of infection nursing, and diabetes patients, who are at a high risk of infection and require extra caution in wound management, are major recipients of infection-related nursing care [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%